PENYULUHAN SELF READINESS TERHADAP BENCANA KEBAKARAN PADA ANAK USIA DINI - Upik Elok Endang Rasmani; Siti Wahyuningsih; Yuanita Kristiani Wahyu Widiastuti (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2021)
Fire is a dangerous threat and can result in the loss of a person's life and material loss. Early childhood is very risky to become victims of fire so there is a need for counseling and assistance to children as provisions in preventing casualties. This research is focused on the socialization of early childhood understanding of the dangers and prevention of fires that have occurred recently. This study uses a qualitative approach with a socialization model. The data was obtained by observation and interviews using Google Form involving resource persons consisting of the principal, teachers of class B. This study revealed that the socialization of early childhood understanding regarding the dangers and fire prevention is very necessary as an effort to prepare for prevention and provision of children's readiness to face fire disaster that can happen at any time.